Evaluasi Pengelolaan Obat Di Instalasi Farmasi RSUD Dr. Soeratno Gemolong Kabupaten Sragen - Diana Putri Arfianingsih; Isna Nur K; Kusumaningtyas Siwi Artini (Pusat Riset dan Inovasi Nasional, 2023)
Drug management is a cycle including selection, procurement, distribution and use which is supported by an appropriate organizational structure, finances and management information system. The aim of this research is to determine drug management in the Pharmacy Installation at RSUD dr. Soeratno Gemolong, Sragen Regency.This research uses prospective and retrospective methods. Where retrospective data is taken from 2022 data. Prospective data is taken through direct observation. The results of this research are: the percentage of available funds and the required funds is 80%, the percentage of procurement and actual use is 98%, invoice errors are 0.47%, there are no delayed payments by hospitals, compatibility between drugs and stock cards is 100% , drug availability level of 16 months, warehouse management system with FIFO, FEFO and LASA marking systems, average time used to serve compounded prescriptions is 11 minutes and non-mixed prescriptions is 7 minutes, conformity of drug items with the National Formulary is 93%, frequency of procurement of each drug item 4-6x a year, turn over ratio 3 times, percentage of expired and damaged drug value 5.05%, dead stock percentage 3%, number of drug items per prescription sheet 3.5 items, percentage of prescriptions with generic names 88%. These results indicate that drug management in the Pharmacy Installation at RSUD dr. Soeratno Gemolong, Sragen Regency is not yet good.